Study of effect of immunosuppresion caused by H9N2 in broiler - Allawe, Aida Bara (The Iraqi Journal of Veterinary Medicine, 2008)
This study was concerned with conduction of experiment for thesereason three groups of broiler chicks were used.First group (which consisted of 15 chicks) was vaccinated with liveattenuated vaccine (laSota strain) at age 10, 20, 30 days by drinkingwater. Second group (which consisted of 15 chicks) was infectedexperimentally with H9N2 (AMR.ANT/IRAQ/2005) 108.6 LD50/0.1mlat age 8 day then vaccinated with live attenuated vaccine (LaSota strain)at age 10, 20, 30 days by drinking water .third group (which consisted of10 chicks) was considered as a control group without vaccination.Immune response in all chicks groups were estimated at age (40) daysdepending on Heamagglutination test and ELISA. The first group showedhighest titer in HI and ELISA tests in comparison with second and thirdgroups.